Thoracoscopic Lobectomy Versus Sublobar Resection for pStage I Geriatric Non-Small Cell Lung Cancer - Lin, Young-Jen; Chiang, Xu-Heng; Lu, Tzu-Pin; Hsieh, Min-Shu; Lin, Mong-Wei; Hsu, Hsao-Hsun; Chen, Jin-Shing (Frontiers in Oncology, 2022)
Objectives: The choice of resection method for geriatric patients with early-stage non-small cell lung cancer (NSCLC) remains contentious. This study aimed to evaluate survival and perioperative outcomes after thoracoscopic lobectomy resection (LR) or sublobar resection (SR) in patients aged ≥75 years with pathologic stage (pStage) I NSCLC. Materials and Methods: We retrospectively examined 258 consecutive patients aged ≥75 years with pStage I NSCLC who underwent thoracoscopic tumor resection at our institute from 2011 to 2018. Propensity score matching (PSM) analysis identified 60 patients in each group for comparison of survival-related parameters, including disease-free survival (DFS), lung cancer-specific overall survival (OS), and non-lung cancer-specific OS, using the Kaplan-Meier analysis. Results: LR and SR were performed in 84 (32.6%) and 174 (67.4%) patients aged ≥75 years, respectively. The LR group had younger patients, better performance status, larger tumor sizes, and deeper tumor location than the SR group. Multivariate studies showed that the resection method was not a prognostic factor for OS. The two PSM-matched groups were not significantly different with respect to lung cancer-specific OS (p = 0.116), non-lung cancer-specific OS (p = 0.408), and DFS (p = 0.597). SR helped achieve better perioperative outcomes than LR, including fewer postoperative complications (10.0% vs. 23.8%, p = 0.011), shorter operative times (p < 0.001), decreased blood loss (p = 0.026), and shorter chest tube duration (p = 0.010) and hospital stays (p = 0.035). Conclusions: Thoracoscopic SR may provide similar oncological outcomes to LR, but may be a safer and more feasible surgical method for geriatric patients with pStage I NSCLC.